2001
DOI: 10.1002/jbm.1236
|View full text |Cite
|
Sign up to set email alerts
|

PMMA‐based bioactive cement: Effect of glass bead filler content and histological change with time

Abstract: A new bioactive bone cement (designated GBC), which is a polymethyl methacrylate (PMMA)-based composite consisting of bioactive glass beads as an inorganic filler and high molecular-weight PMMA as an organic matrix, has been developed. The purpose of the present study was to evaluate the effect of the filler content on the mechanical properties and osteoconductivity of GBC, to decide the most suitable filler proportion, and to evaluate the degree of cement degradation with time. The bioactive beads, consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…A low-signal layer, which may be a sign of degradation, as reported previously, 7,15 was observed in SEM photographs of the cementbone interface with both GBC(F ϩ) and GBC(F Ϫ . SEM photographs of (a) GBC(F ϩ) at 4 weeks after implantation, (b) GBC(F Ϫ) at 4 weeks, and (c) hPMMA at 4 weeks in rat tibiae.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…A low-signal layer, which may be a sign of degradation, as reported previously, 7,15 was observed in SEM photographs of the cementbone interface with both GBC(F ϩ) and GBC(F Ϫ . SEM photographs of (a) GBC(F ϩ) at 4 weeks after implantation, (b) GBC(F Ϫ) at 4 weeks, and (c) hPMMA at 4 weeks in rat tibiae.…”
Section: Discussionmentioning
confidence: 50%
“…7,8 The bending strength of GBC (approximately 130 MPa) 7,11,15 became higher than that of conventional PMMA cement (92 MPa). 21 A further important advantage is that the handling properties of GBC are as good as those of PMMA bone cement.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the Young's moduli of GBC50 and GBC60 were significantly higher than those of CMW-1 at all time points. Although high Young's modulus values are not in themselves an advantage, because high elastic moduli can be associated with uneven stress distribution or load transmission between a prosthesis and the bone, 11,15,23 GBC was believed to retain its ductility. In a previous study, GBC was packed into the intramedullary canals of rat tibiae and found found to have excellent osteoconductivity.…”
Section: Discussionmentioning
confidence: 98%
“…After soaking in phosphate-buffered saline solution (PBS) for one day, their bending strength was tested on a materials testing machine (model AG-10TB; Shimadzu Co., Kyoto, Japan), run at a cross-head speed of 0.5 mm/min, with the use of the three-point bending method. 7,[11][12][13][14][15][16][17] The values for Young's modulus were derived from the stress-strain curves obtained from the bending test results.…”
Section: Initial Mechanical Testing Of the Cement Specimensmentioning
confidence: 99%